2009
DOI: 10.1007/s12524-009-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based analysis of the role of land use/land cover and vegetation density on surface temperature regime of Delhi, India

Abstract: The knowledge of the surface temperature is important to a range of issues and themes in earth sciences central to urban climatology, global environmental change and human-environment interactions. The study analyses land surface temperature (LST) estimation using temporal ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) datasets (day time and night time) over National Capital Territory Delhi using the surface emissivity information at pixel level. The spatial variations of LST over diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 7 publications
4
19
0
Order By: Relevance
“…According to them, the LST ranged from 22.2 °C to 46 °C with west and south-western part of Delhi exhibiting the highest surface temperature (35-44 °C). Kant et al [21] analyzed LST using ASTER datasets for Delhi using the 22 September 2003 images and observed parallel results. On the basis of analysis of 80 samples points selected for all the four seasons, it is found that the overall average surface temperature is lowest in January and highest in May.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…According to them, the LST ranged from 22.2 °C to 46 °C with west and south-western part of Delhi exhibiting the highest surface temperature (35-44 °C). Kant et al [21] analyzed LST using ASTER datasets for Delhi using the 22 September 2003 images and observed parallel results. On the basis of analysis of 80 samples points selected for all the four seasons, it is found that the overall average surface temperature is lowest in January and highest in May.…”
Section: Resultsmentioning
confidence: 92%
“…Summers are long and extremely hot accompanied with frequent dust storms. Humidity level is high during the monsoon season, while the air is dry during the rest of the year [21,40]. For the purpose of governance and management, Delhi is divided into nine districts and 27 tehsils/sub-divisions.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main causes of global climate change is increasing industrialization and urbanization. Currently, the most crucial problem that urban areas suffer from is rising surface temperatures caused by the loss of areas of vegetation and the increase of impermeable non-transpiring, non-evaporating, hard land surfaces [2][3][4][5][6]. One of the most noticeable effects of the modifications of terrestrial ecosystems by human activity is the change in land use/land cover (LULC) as it has greatly impacted the environment locally, regionally and globally [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Issues pertaining to land surface emissivity, LST and NDVI are explored by Mallick et al [24], Mallick et al [25], Sharma and Joshi [26] and Kant et al [27] for Delhi, while a UHI examination for Mumbai is still unexplored. However, analysis of population growth and LU change is examined [28], but not with the help of satellite data.…”
Section: Introductionmentioning
confidence: 99%